Access to Hepatitis C treatment: A global problem - Germán Velásquez (South Centre, 2017)
"Viral hepatitis is an international public health challenge, comparable to other major communicable diseases, including HIV, tuberculosis and malaria. Despite the significant burden it places on communities across all global regions, hepatitis has been largely ignored as a health and development priority until recently". - WHO, Global Health Sector strategy on viral Hepatitis 2016-2021: Towards ending viral hepatitis. This document will address five items: 1) General context and background on the debate over access to medicines. 2) The problem of the Hepatitis C virus (HCV): Figures and data. 3) Access to new direct-acting antiviral (DAA) treatments for Hepatitis C. 4) How to overcome barriers to access: using the flexibilities of the TRIPS Agreement. 5) Some examples of countries that have launched the new HCV treatment and Conclusions.
Keywords: 300; Infektionskrankheit; Gesundheitsversorgung; Arzneimittel; Arzneimittelrecht; Internationales Recht; Welt